Constraining long-term denudation and faulting history in intraplate regions by multisystem thermochronology: An example of the Sudetic Marginal Fault (Bohemian Massif, central Europe) - Danisik, Martin; Stepancikova, P.; Evans, Noreen (American Geophysical Union, 2012)
The Rychlebské hory Mountain region in the Sudetes (NE Bohemian Massif) provides a natural laboratory for studies of postorogenic landscape evolution. This work reveals both the exhumation history of the region and the paleoactivity along the Sudetic Marginal Fault (SMF) using zircon (U-Th)/He (ZHe), apatite fission track (AFT), and apatite (U-Th)/He (AHe) dating of crystalline basement and postorogenic sedimentary samples. Most significantly, and in direct contradiction of traditional paleogeographic reconstructions, this work has found evidence of a large Cretaceous sea and regional burial (to >6.5 km) of the Carboniferous-Permian basement in the Late Cretaceous (~95–80 Ma). During the burial by sediments of the Bohemian Cretaceous Basin System, the SMF acted as a normal fault as documented by offset ZHe ages across the fault. At 85–70 Ma, the basin was inverted, Cretaceous strata eroded, and basement blocks were exhumed to the near surface at a rate of ~300 m/Ma as evidenced by Late Cretaceous–Paleocene AFT ages and thermal modeling results. There is no appreciable difference in AFT and AHe ages across the fault, suggesting that the SMF acted as a reverse fault during exhumation. In the late Eocene–Oligocene, the basement was locally heated to <70°C by magmatic activity related to opening of the Eger rift system. Neogene or younger thermal activity was not recorded in the thermochronological data, confirming that late Cenozoic uplift and erosion of the basement blocks was limited to less than ∼1.5 km in the study area.